Vatican secret diplomacy : Joseph P. Hurley and Pope Pius XII - Gallagher, Charles R., 1965- (Yale University Press, 2008)
In the corridors of the Vatican on the eve of World War II, American Catholic priest Joseph Patrick Hurley found himself in the midst of secret diplomatic dealings and intense debate. Hurley's deeply felt American.